The China Tax Guide - Devonshire-Ellis, Chris; Scott, Andy; Woollard, Sam (China Briefing, The Practical Application of China Business, 2011)
This guide is a practical overview for the international businessman to understand the rules, regulations and management issues regarding taxes in China. It is written very much from practical experience. We will help you to understand the implications of what can initially appear be a complicated and contradictory subject. This book tells you the basics of what you need to know, and point you at the structures you should use to enable your China business to be both in compliance and as tax efficient as possible.